Involvement of miR-3180-3p and miR-4632-5p in palmitic acid-induced insulin resistance. (20th August 2021) - Tashiro, Etsu; Nagasawa, Yumi; Itoh, Susumu; Imoto, Masaya
Abstract: Insulin resistance is defined as a failure to trigger the activation of the PI3K-AKT pathway by normal levels of insulin; therefore, it is well linked to metabolic disorders. Although multiple mechanisms contribute to insulin resistance, one major cause is elevated concentrations of plasma free fatty acids, which are known to suppress insulin signaling. However, the underlying mechanism is still elusive. Here, we found that palmitic acid increased the expression of two miRNAs, miR-3180-3p and miR-4632-5p, in HepG2 cells. Transfection of HepG2 cells with miR-3180-3p or miR-4632-5p reduced insulin-induced activation of the PI3K-AKT pathway. Moreover, palmitic acid or two miRNAs inhibited insulin-induced phosphorylation of Tyr612 on IRS-1 without affecting insulin receptor activation. Therefore, two miRNAs are suggested to be involved in palmitic acid-induced insulin resistance through suppression of insulin-induced IRS-1 phosphorylation. Identification of miR-3180-3p and miR-4632-5p targets could provide valuable information for the development of therapeutic drugs for type 2 diabetes. Highlights: MicroRNAs are involved in palmitic acid-induced insulin resistance. Palmitic acid increases the expression of miR-3180-3p and miR-4632-5p. MiR-3180-3p and miR-4632-5p suppresses insulin-induced phosphorylation of IRS-1.